Higher Education in Times of Instability and Disruption: Rethinking Notions of Values, Value Creation and Instructional Practices in Vietnam and Beyond - Felix, Jonathan J. (Frontiers in Communication, 2021)
The disruptive nature of the COVID-19 pandemic has created a massive shift in instructional practices in higher education across the globe. The impact of this pandemic on education globally has led to a surge in online teaching and the use of various digital technologies and platforms to support instructional practices. However, this world-changing event has foregrounded the limitations of technology in addition to other important indications, particularly as it relates to the notion of value and by extension value creation. Within the context of the Vietnamese higher education ecosystem, what is evident is that a re-evaluation of values is worth considering, in terms of the value of local higher education institutions, in addition to the value creation produced by the same. This article will engage with pertinent implications for the post-COVID realities which offer untold challenges and opportunities in Vietnam and elsewhere. Moreover, the post-COVID realities of late modernity only serve to accentuate the importance of values and value creation in this context as higher education institutions would re-evaluate, rethink, and retool approaches to instructional practices. A focus on questions of value aids in considering the broader conditions and contexts which support some of the fruitful and situated outcomes of higher education which includes human capital development, employment, social mobility and the production of modern social identities.